Systematic review on determinants of therapeutic adherence in individuals from 50 to 69 years of age - Bicudo, Carlos de Aguiar da Câmara Salema (2022)
Trabalho Final do Mestrado Integrado em Medicina apresentado à Faculdade de Medicina